The Debate after the White Book about the Future of EU Expectations and Results - Moraliyska, Monika (Research Papers, 2018)
The aim of the study is to analyze the White Paper on the future of the EU and to answer whether it has managed to trigger the desired debate. The tasks are: analysis of the scenarios in terms of the degree of integration and the consequences thereof; exploring the views of different stakeholders; analysis of different member states’ positions on the Paper. The methodology includes analysis and synthesis, induction and deduction, etc. The limitations are related to the rapidly changing information and its inability to be traced in the Member States.